Effect of solubilization technique on dissolution - Das, Sujoy; Bahadur, Sanjib; Choudhury, Ananta; Saha, Suman (Journal of Applied Pharmaceutical Research, 2014)
More than 40 percent of newly discovered drugs have little or no water solubility thus the present research aimed at the study of improvement of solublisation on dissolution by addition of different solublising agents and modification of methods. Irbesartan is the drug of choice. Effect of Solubility on dissolution was studied with some solubilizing agents like β-Cyclodextrins, PEG-6000, Polysorbate-80, Cremophore and Resins (Doshion). It was seen that Irbesartan give 90 percent release in 1hr with polysorbate-80 where cremophore containing tablets showed 97 % release in 1 hr in case of solid dispersion technique and in case of complexation technique respectively. Thus the present study concluded that, dissolution rate of poorly soluble drug can be increases by using solubilizing agent as well as using different techniques